Dispersion analysis of two-dimensional unstructured transmission line modelling (UTLM) - Khashan, Lamia M.A. (2015)
Numerical simulation techniques play an important role due to their flexibility in dealing with a broad range of complex geometries and material responses. This flexibility requires substantial computational time and memory. Most numerical methods use structured grid for graphical discretization, although this approach is straightforward it is not ideal for smoothly curved boundaries.